Assessment of E-Waste Management and Potential for Laptop Reuse and Recycling - Giao Thanh Nguyen; Trinh Thi Kieu Lam; Nhien Thi Hong Huynh (Salehan Institute of Higher Education, 2023)
Reusing and recycling laptops has many positive benefits, both environmentally and economically. Therefore, this study was conducted with the objectives of assessing (1) the current state of ownership, (2) the current state of use and disposal, and (3) quantifying the potential reuse and recycling of laptops for students at Can Tho University, Vietnam. Based on data collected by document review and face-to-face interviews with students, with a usage rate of 1 laptop per student, it is estimated that the whole of Can Tho University has 42,918 laptops in use. The actual use lifespan of the laptop is 5.28 years, lower than the expected lifespan of 6.8 years. The results of the correlation analysis show that the actual usage life does not have any correlation with the consumption behavior of students. In addition, the study estimates that 96.67% of laptops will be disposed of before 2031. In which, the potential for direct reuse is 2.33%, reuse with support is 88.33%, and recycling is 9.33%. The results show that universities have great potential to implement safe e-waste collection and treatment activities. Doi: 10.28991/CEJ-2023-09-06-013 Full Text: PDF